Out-Of-School Children Initiative (OOSCI) - Young, Roy A.; Macfarlane, Victoria; Aldana, Martin (United Nations Children’s Fund (UNICEF), Belize, 2017)
The Five Dimensions of Exclusion (5DE) are central to the OOSCI approach, presenting groups of children for analysis and interventions. Three of the dimensions represent children who are out-of-school, as follows: • Dimension 1: Children of pre-primary school age who are not in pre-primary or primary school. • Dimension 2: Children of primary school age who are not in primary or secondary school. • Dimension 3: Children of lower secondary school age who are not in primary or secondary school. Two dimensions are represented by children in school but at risk of dropping out, as follows: • Dimension 4: Children who are in primary school but at risk of dropping out. • Dimension 5: Children who are in lower secondary school but at risk of dropping out.
Keywords: school dropouts; primary school; secondary school; children